Design and implementation of TOF (Tool Open Fan) to improve maintenance efficiency of exhaust fan in gland steam condenser at steam power plants - Deden Mamun Sajaah; Aulia Ramadhan; Dodi Sofyan Arief (BKS-TM Indonesia, 2025)
This paper presents the design and implementation of TOF (Tool Open Fan) as an innovative solution to enhance the maintenance efficiency of exhaust fans in gland steam condensers (GSC) at coal-fired steam power plants. Conventional disassembly using puller tools often caused mechanical damage to the fan surface, leading to costly replacements and downtime of up to 38 days. The TOF tool was designed with an adjustable house, fix house, and jack bolt mechanism to provide safe, ergonomic, and efficient fan disassembly. Finite element simulations were conducted to analyze stress distribution on both the tool and the fan. Implementation at PLTU Tenayan demonstrated a significant reduction in maintenance duration, from 9 hours to 3 minutes, and reduced manpower from five to two workers. Financially, the innovation generated a saving of approximately IDR 104,500,000 per exhaust fan by avoiding unnecessary replacement. The study concludes that TOF offers both economic and safety benefits, contributing to power plant reliability and sustainable maintenance practices. Limitations include the need for further design adjustments for compatibility with different GSC configurations across power plants.